The impact of strength training on the improvement of jumping ability and selected power parameters of the lower limbs in soccer players - PATRICIA FISCHEROVA; MAGDALENA NITYCHORUK; WOJCIECH SMOLKA; MARCIN ZAK; ARTUR GOLAS; ADAM MASZCZYK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Introduction: The aim of the study was to compare the impact of a 6-week program combined with football training and strength training on strength and power parameters in highly trained soccer players. It was hypothesized that 6 weeks would be enough for the experimental group to improve their jumping ability and pushing power. Material and methods: The study involved 34 female footballers playing in Ekstraliga (age: 22 ± 5 years; body height: 167 ± 5 cm; body weight: 60 ± 8 kg). The contestants were divided into an experimental group and a control group of 17 people in each group. The control group performed football trainings combined with 2 additional strength units (50% 1RM load) 3 times a week. The experimental group, apart from football trainings, additionally performed 2 strength trainings per week (50-85% 1RM load). Results: The results of the experiment show a significant improvement in the height of the vertical jump and bench press while sitting in the experimental group CMJ (p <0.05; p = 0.000029; ES: 1.00; 11%), CMJA (p <0.05; p = 0 00003; ES = 1.09; 13%), and LP (p <0.05; p = 0.027681; ES = 0.48; 6%), while in the control group the changes in the results after the training program were statistically insignificant CMJ (p> 0.05; p = 0.274000; ES: 0.07, 1%), CMJA (p> 0.05; p = 0.350958 ES = 0.27, 3%), and LP (p> 0.05; p = 0.130153; ES = 0.27; 4%). Conclusion: The presented research results suggest that a short, six-week training program including general football training and strength training performed twice a week with loads gradually increasing during the preparatory period may significantly improve the strength and jumping parameters of the lower limbs in soccer players. Such information can be valuable at the stage of training in the field of special skills training in football.